Analisis Dialek Kansai Pada karakter Inuyama Aoi dalam Anime Yuru Camp : An Analysis of Inuyama Aoi's Use of The Kansai Dialect in The Anime Yuru Camp - Diner, Lispridona; Andriyanto, Fathoni; Tama, Marzusa Surya; Setiawan, Wahyu (Jurnal Pendidikan Bahasa Jepang Undiksha, 2025)
Dialect is one of the forms of language variation that reflects the social and geographical identity of its speakers, and it plays an important role in cultural representation in media, including anime. The Kansai dialect, spoken in Japan's Kansai region, varies from standard Japanese in phonetics, grammar, and vocabulary. By analyzing Inuyama Aoi's dialogues, the study aims to understand how the Kansai dialect shapes her character and influences viewers' perceptions. The methodology involves transcribing and analyzing her dialogues to identify distinctive Kansai dialect features such as pitch accent, grammar, and vocabulary. The study seeks to reveal how the dialect contributes to portraying Inuyama Aoi's personality and background. Initial findings indicate that the Kansai dialect highlights her regional identity and cultural background, enhances the anime's authenticity, and adds humor and warmth to her character. This research deepens our understanding of dialects in anime and their role in character development, providing insights into nuanced and authentic character portrayals.